Comparative Evaluation of Lithuanian Economic Development - Bivainis, Juozas (Ekonomika, 2001)
The article is devoted for introduction of the economic development of Lithuania after the re-establishment of the Independence. There is presented the description of economic performance during the period 1990-2000; it is done by comparison with other European countries. The economy of Lithuania has undergone three different stages of essential changes in all it’s sectors: the year 1991-1993 - a period of dramatic decline so habitual phenomenon in all postcommunist countries; the year 1994-1998 - a period of recovery: the economy was stabilised and began grow in relatively fast steps; the year 1995-2000 - a period of unexpected decline (influence of the crisis of the Russian finance) and very slow recovery. The main used indicators sufficiently reflect mentioned stages of the economic development of the country. The Republic of Lithuania bas made significant progress. The achievements of the state in the area of economic stabilisation are obvious: the inflation rate has been reduced considerably and is near to be close to required convergence level. Preconditions for the implementation of the structural reforms were created by liberalisation of prices, legalisation of private ownership and creation of financial sector. Although the private sector is dominant, but till now efficiency of companies has remained insufficient. The economy suffers with problems caused by the poor process of restructuring of companies as well as finance institutions. A big amount of industrial companies are loss-making as well as an obvious obstacle for economic stability. The opportunities to solve problems in the industrial sector are strongly dependent from financial and social environment. Improvements in competition environment as well as in taxation policy or infrastructure are to be done. The agricultural sector till now has remained with low efficiency in all type farms. An urgent growth of unemployment in rural area demands special attention. It is evident that the agricultural sector requires modernisation and technological reorganisation as well as introduction of innovations with promotion of it’s production competitiveness in domestic and foreign markets. The comparison of indicators, describing the economic development of Lithuania with the ones of the other European countries is resulted by main conclusions: 1) The level of economic development in the all three Baltic states is very similar in spite of different ways of implementation of economic reforms as well as varieties in liberalisation and macroeconomic policy or patterns of privatisation and restructuring; 2) The Republic of Lithuania has similar background if compare with the other states which apply for the EU membership; our country occupies middle position in the list by the annual growth of the GDP, the most integrated indicator of economic development, during the last years; 3) The Republic of Lithuania is backward from the states-members of the EU by various aspects. Were estimated macroeconomic indicators such as GDP per capita according to purchasing power parity, average monthly wages, et.; 4) The integration into the EU is to be the main factor for higher convergence of the economic development levels between the Republic of Lithuania and the EU countries.